2014
DOI: 10.1108/jsma-03-2013-0017
|View full text |Cite
|
Sign up to set email alerts
|

Value creation through cross-border mergers and acquisitions by the Indian pharmaceutical firms

Abstract: Purpose – Cross-border mergers and acquisitions (M&A) have given the opportunity to the emerging market multinationals to add value while implementing the strategy of internationalization. The Indian pharmaceutical firms are also adopting this strategy and the purpose of this paper is to determine the evidence of value creation for their international M&A activity. Design/methodology/approach – In total, 30 cross-border M&A a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 63 publications
1
13
0
Order By: Relevance
“…This result is consistent with the results of some studies (Kumar, 1984;Healy et al, 1992;Chatterjee and Meeks, 1996;Ghosh, 2001;Srivastava and Prakash, 2014). However, it is not consistent with the results of some other studies that found a decline of the profitability ratios (Meeks, 1977;Salter and Weinhold, 1979;Mueller, 1980;Kusewitt, 1985;Ravenscraft and Scherer, 1987;Dickerson et al, 1997;Sharma and Ho, 2002;Oduro and Agyei, 2013;Pantelidis et al, 2014;Rodionov and Mikhalchuk, 2016 (in crisis periods).…”
Section: Evaluation Of Accounting Performance After Mergersupporting
confidence: 66%
See 1 more Smart Citation
“…This result is consistent with the results of some studies (Kumar, 1984;Healy et al, 1992;Chatterjee and Meeks, 1996;Ghosh, 2001;Srivastava and Prakash, 2014). However, it is not consistent with the results of some other studies that found a decline of the profitability ratios (Meeks, 1977;Salter and Weinhold, 1979;Mueller, 1980;Kusewitt, 1985;Ravenscraft and Scherer, 1987;Dickerson et al, 1997;Sharma and Ho, 2002;Oduro and Agyei, 2013;Pantelidis et al, 2014;Rodionov and Mikhalchuk, 2016 (in crisis periods).…”
Section: Evaluation Of Accounting Performance After Mergersupporting
confidence: 66%
“…Many past studies on post-merger performance that employed accounting ratios and were conducted during the last decades supported an improvement in the corporate performance after the M&As action (Cosh et al, 1980;Parrino and Harris, 1999;Vijayakumar and Sridevi, 2013;Muhammad and Zahid, 2014;Oruc Erdogan and Erdogan, 2014;Rao-Nicholson et al, 2016), while others claimed that there was a deterioration in the post-merger firm performance (Meeks, 1977;Salter and Weinhold, 1979;Mueller, 1980;Kusewitt, 1985;Ravenscraft and Scherer, 1987;Dickerson et al, 1997;Sharma and Ho, 2002;Oduro and Agyei, 2013), and some others concluded a "zero" result or ambiguous results from the M&As action (Kumar, 1984;Healy et al, 1992;Chatterjee and Meeks, 1996;Ghosh, 2001;Srivastava and Prakash, 2014;Rodionov and Mikhalchuk, 2016).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Acquisition of companies with huge R&D investments facilitates the accumulation of technology and innovation resources and the development of competitive advantages. The research of R. Srivastava and A. Prakash [41] proved a significant positive impact of R&D intensity on M&A performance on the basis of 187 mergers and acquisitions initiated by Indian pharmaceutical companies. A positive but statistically insignificant influence of R&D intensity on M&A performance was found by X. Wu et al [40] using a selection of data on 180 cross-border mergers and acquisitions made by Chinese companies in 2002-2012, as well earlier by M. Hassan et al [39].…”
Section: Literature Review Of Impact Of Intellectual Capital On Manda Pmentioning
confidence: 99%
“…One way to fund the firm is by borrowing money to leverage the ability of the company to survive. Based on Srivastava & Prakash (2014), leverage can indicate the expenditure, and it will show that the company launches the new product. The debt ratio is used in this research as the control variable, to show the efficiency of using borrowed capital.…”
Section: Jurnal Keuangan Dan Perbankan | Financementioning
confidence: 99%